Integration of World Stock Market an Emperical Investigation - Nalini Prava Tripathy (Universitas Islam Indonesia, 2006)
This paper has analyzed the integration of world stock market with emerging mar-ket by using the Granger Causality test and Johansens co integration test. This paper has found one-way significant causality between some of the emerging markets with world mar-kets and concludes that some of the emerging markets have long term equilibrium relation-ship with world stock market.Key words: world market, emerging market, causality test, Johansens co integration test